2017
DOI: 10.1038/srep40994
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of galectin-1, galectin-3, and galectin-9 are associated with large artery atherosclerotic stroke

Abstract: The aim of this study was to assess the expression patterns of serum galectin-1 (Gal-1), galectin-3 (Gal-3), galectin-9 (Gal-9), and galectin-3 binding protein (Gal-3BP) and their associations with stroke outcome in large artery atherosclerotic (LAA) stroke. The serum levels of Gal-1, Gal-3, Gal-9, and Gal-3BP were measured by ELISA in 130 patients with LAA stroke and 130 age- and sex-matched controls. Serum samples were collected from the patients on day 1, day 6, and in the 4th week after ischaemic stroke (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 52 publications
4
49
1
1
Order By: Relevance
“…This observation is consistent with previously published concentration ranges of exogenous Gal3 required to rescue the uptake of CD44 on Gal3depleted cells 33 . These nanomolar concentrations are also in line with the amount of Gal8 and other galectins found in the serum of healthy individuals and cancer patients 37,38 . Together, these data demonstrate that the endocytosis of CD166 is dependent on Gal8 and glycosphingolipids, a typical feature of endocytic processes that operate according to the GL-Lect hypothesis.…”
Section: Quantitative Proteomics Of Cell Surface Upon Cme Inhibitionsupporting
confidence: 77%
“…This observation is consistent with previously published concentration ranges of exogenous Gal3 required to rescue the uptake of CD44 on Gal3depleted cells 33 . These nanomolar concentrations are also in line with the amount of Gal8 and other galectins found in the serum of healthy individuals and cancer patients 37,38 . Together, these data demonstrate that the endocytosis of CD166 is dependent on Gal8 and glycosphingolipids, a typical feature of endocytic processes that operate according to the GL-Lect hypothesis.…”
Section: Quantitative Proteomics Of Cell Surface Upon Cme Inhibitionsupporting
confidence: 77%
“…Several proteins from the galectin family were found to be significantly correlated with TMAO, including galectin-9 and galectin-3 (r = 0.18, p < 10 À3 ; r = 0.12, p < 0.05, respectively), which were both shown to be higher in the serum of atherosclerotic stroke patients compared to controls (He et al, 2017). Additional significantly associated proteins were adrenomedullin (r = 0.18, p < 10 À3 ), a protein reported to be higher in patients suffering from cardiovascular or kidney disease (Bunton et al, 2004;Ishimitsu et al, 1994), and kidney injury molecule 1 (r = 0.17, p < 10 À2 ), a protein that has been shown to be induced in experimental kidney injury and in biopsies of renal disease (van Timmeren et al, 2007;Waanders et al, 2010).…”
Section: Proteins Associated With Cardiovascular and Kidney Disease Amentioning
confidence: 97%
“…Gal-3, therefore, appears to be a crucial mediator of the GI damage observed after brain injuries, directly at the level of enteric neuronal cells and it may represent a potential new target for the treatment of post-stroke gastrointestinal complications. In this regard, it has been recently reported that elevated serum levels of Gal-3 correlates with poor outcome after acute heart failure and high Gal-3 values are observed in heart failure patients with a history of stroke [ 231 ].…”
mentioning
confidence: 99%